Dulce Mothers: an intervention to reduce diabetes and cardiovascular risk in Latinas after gestational diabetes. Issue 1 (28th January 2014) - Philis-Tsimikas, Athena; Fortmann, Addie L.; Dharkar-Surber, Sapna; Euyoque, Johanna A.; Ruiz, Monica; Schultz, James; Gallo, Linda C.
Abstract: Latina women with prior gestational diabetes mellitus (GDM) are at elevated risk for type 2 diabetes mellitus and cardiovascular disease. Few primary prevention programs are designed for low socioeconomic status, Spanish-speaking populations. We examined the effectiveness of a Diabetes Prevention Program (DPP) translation in low-income Latinas with a history of GDM. Eighty-four Latinas, 18–45 years old with GDM in the past 3 years, underwent an 8-week peer-educator-led group intervention, with tailoring for Latino culture and recent motherhood. Lifestyle changes and diabetes and cardiovascular risk factors were assessed at study baseline, month 3 and month 6. Participants showed significant improvements in lipids, blood pressure, physical activity, dietary fat intake, and fatalistic and cultural diabetes beliefs ( p < 0.05). Formative evaluation provides preliminary evidence of program acceptability. A peer-led, culturally appropriate DPP translation was effective in improving lifestyle changes and some indicators of cardiovascular and diabetes risk in Latinas with GDM.